1939
DOI: 10.1111/j.1469-185x.1939.tb00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Keimblattchimärenforschung an Seeigellarven

Abstract: Summary When skeleton‐forming cells of a donor sea urchin embryo are transplanted into a host embryo of another species, whose endoderm and mesoderm have previously been removed so that it only possesses ectoderm, a larva may be produced which is a chimaera consisting only of skin and skeleton. The donor skeleton is harmoniously situated in the host larva, thanks to the influence of the latter. But the skeleton affects the host inasmuch as it forces the latter to form larval processes. The skeletal structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1943
1943
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, the majority of works that Rensch relies on pertain to what was already called in the mid-century "classical experimental embryology" (Oppenheimer, 1955). (Horstadius, 1939;Ubisch, 1939). Rensch also provides clearer examples of archallaxis between closely related species without important differences in the adult phenotype, such as the related species of worms Tubifex rivulorum and pachydrilus lineatus, studied by Andreas Penners, which differ in their type of cleavage and in most later stages of development (Penners, 1922(Penners, , 1930.…”
Section: )mentioning
confidence: 99%
“…However, the majority of works that Rensch relies on pertain to what was already called in the mid-century "classical experimental embryology" (Oppenheimer, 1955). (Horstadius, 1939;Ubisch, 1939). Rensch also provides clearer examples of archallaxis between closely related species without important differences in the adult phenotype, such as the related species of worms Tubifex rivulorum and pachydrilus lineatus, studied by Andreas Penners, which differ in their type of cleavage and in most later stages of development (Penners, 1922(Penners, , 1930.…”
Section: )mentioning
confidence: 99%
“…This means that Ciona tail bending occurs independently without external force (Hotta et al, 2007a; Lu et al, 2020). Although it has been shown that a longitudinal pushing force is exerted by each notochord cell (Sehring et al, 2014; Zhou et al, 2015) and the tail elongation has suggested that the notochord actively produces an AP elongating force (Miyamoto and Crowther, 1985; Sehring et al, 2014; Spemann, 1987; Ubisch, 1939), the mechanism of tail bending in the tailbud embryo has been unknown until a recent study by Lu et al (2020). They investigated the internal molecular mechanism that enables Ciona to bend its tail of early tailbud and reported that the main factor of the tail bending during early tailbud stages (stage 18 to stage 20) is that the different contraction force by the actomyosin in between the ventral and the dorsal side of the notochord.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that an AP pushing force is exerted by each notochord cell (Sehring et al, 2014;Zhou et al, 2015), and that tail elongation is achieved by the notochord actively producing AP elongating forces (Miyamoto and Crowther, 1985;Sehring et al, 2014;Spemann, 1987;Ubisch, 1939), the mechanism by which the tail bends in the tailbud stage embryo is only incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gustafson and Wolpert () described the behavior of skeletogenic cells as they migrated inside the blastocoel in preparation for skeletogenesis, and Okazaki () showed that many of those same behaviors occurred when PMCs were placed in vitro . The Okazaki work and earlier work by von Ubisch () and Baltzer et al . () supported the hypothesis that autonomous patterning mechanisms were programmed into the skeletogenic cells.…”
mentioning
confidence: 97%